ACTIVATED SLUDGE PROCESS OF WASTEWATER TREATMENT PLANT - Aburzizah, Asaad Seraj; Aljohani, Fahad Salih (Journal of natural sciences, life and applied sciences, 2019)
Wastewater may be described as water that was used to convey pollutants away from a source of pollution. It originates in homes, businesses, schools, hospitals, prisons, and industries, and was ultimately discharged back into the environment. Solids are present in nearly every wastewater, may be very detrimental environmentally, and so are very often regulated in discharges of wastewater. The aimed of this study was to intend the usage of the Activated Sludge Process Control and operating the activated sludge process, including nutrient removal, and troubleshooting. This study was contacted with Saudi Arabia waste water plants as guideline for maintenance and troubleshoots. When troubleshooting activated sludge problems, was to overlook obvious sources and solutions in favor of the strange and unusual.
Keywords: Biochemical Oxygen Demand; wastewater treatment plant; the carbonaceous oxygen demand